"Using unity and victory to bid farewell": China's management of the public opinion incident of Dr Li Wenliang through crisis nationalism. Issue 1 (November 2022) - Zhang, Chunyu; Zhu, Runhua; Mo, Shiwei
This paper examines how online expressions about Dr Li Wenliang became a public opinion incident in China and how the regime adjusted its internet censorship and emotional governance. We find that public perception of Li changed from a rumormonger to a whistleblower, a victim of structural causes, and a martyr of the nation, with collective emotions shifting from feelings of uncertainty to outrage, panic, and grief. Reassured by the state's crisis management and by positive stories of solidarity and resilience, the public then moved to a xenophobic discourse of crisis nationalism with feelings of hope, vindication, and pride. Meanwhile, public trust in the state grew as the regime delegated responsibility to local governments and perpetuated itself as a paternalistic, responsive, and effective leader through an authoritarian participatory propaganda. We argue that the pandemic spawned an emerging crisis nationalism that fed into the regime's crisis management and propaganda.